Study of altitude and selection on fiber biometry properties of Fagus orientalis Lipsky - ZOHREH ZOGHI; DAVOUD AZADFAR; ALI KHAZAEIAN (Nusantara Bioscience, 2013)
Abstract. Zoghi Z, Azadfar D, Khazaeian A. 2013. Study of altitude and selection on fiber biometry properties of Fagus orientalis Lipsky. Nusantara Bioscience 5: 30-34. This research reports to the influence of altitude above sea level and selection on fiber biometry of beech wood (Fagus orientalis Lipsky). In this research, six trees in 550 MASL (three plus trees and three non-plus trees) and six trees in 850 MASL (three plus trees and three non-plus trees) were selected. One sample from each tree was gotten with increment borer at breast height. Fiber characteristics such as fiber length, fiber diameter, lumen width, and two wall thicknesses were measured in Franklin method. Slenderness ratio, flexibility ratio and rankle ratio were estimated. The results showed that the altitude had a significant effect on fiber length, lumen width, wall thickness, and biometry coefficients. Tree quality has a significant effect on fiber length, lumen width, and wall thicknesses and biometry coefficients. Fiber length, lumen width, slenderness ratio and flexibility ratio in plus trees were more than non-plus tree.